Morphological variation and sex dimorphism in adult Аzov Yellow-legged Gull Larus cachinnans сachinnans - Neubauer, G.; Koshelev, A.I.; Koshelev, V.A.; Zagalska, M. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2001)
Gulls were trapped in the breeding colony on islands of Molochny Liman, a salt reservoir near the north Azov seashore (south of Zaporizhzhia Region, Ukraine). The total of measured cachinnans is 80 birds, more than 3500 nestlings were ringed. For trapped birds a total of 28 parameters were taken (14 metrical and 14 colour features). Blood samples were obtained from the most of the captured birds for further genetical analysis, and pictures were taken to record coloration (colour of eyes, legs, mantle, etc.). Исследования проводились в 2000-2001 гг. на юге Запорожской области, на о-вах Молочного лимана Азовского моря. Сетевыми ловушками типа «цилиндр» было отловлено, прижизненно обследовано и окольцовано 80 экз. взрослых чаек, окольцовано свыше 3500 подросших птенцов. Измерения проводились по 28 параметрам (14 метрических и 14 цветовых). Брались пробы крови из ножной вены для последующего генетического анализа, проведена цветная фотосъемка внешнего вида чаек (окраска глаз, ног, мантии и др.). Дослідження проводилися в 2000-2001 рр. на півдні Запорізької області, на о-вах Молочного лиману Азовського моря. Сітковими пастками типу «циліндр» було виловлено, прижиттєво обстежено та закільцьовано 80 екз. дорослих мартинів, закільцьовано понад 3500 підрослих пташенят. Виміри проводилися згідно з 28 параметрами (14 метричних і 14 колірних). Бралися проби крові з ножною вени для подальшого генетичного аналізу, проведена кольорова фотозйомка зовнішнього вигляду чайок (забарвлення очей, ніг, мантії та ін.).